Guide to the UNFCCC negotiations on Agriculture - CGIAR Research Program on Climate Change, Agriculture and Food Security; Technical Centre for Agricultural and Rural Cooperation; Farming First (2013)
The aim of the set of tools on these pages is to provide knowledge, information and support to various stages of an advocacy campaign focused on the importance of agriculture within climate change negotiations. The components of a campaign include: Key Messages, Agriculture & the UNFCCC, Raising key issues, Examples. The Guide to UNFCCC Negotiations on Agriculture: Toolkit for Communications and Outreach which was published by Farming First, with the support of contributors: the CGIAR Research Program on Climate Change, Agriculture and Food Security (CCAFS) and the Technical Centre for Agriculture and Rural Cooperation (CTA).